Parental Perceptions of the Impact of Having a Child with Autism Spectrum Disorder on Siblings’ Marriage Prospects: A Field Study in Ramallah, Palestine (The International Journal of Educational Sciences and Arts, 2026)
This study examined parental perceptions of how having a child with autism spectrum disorder (ASD) may influence the marriage prospects of other children in the same family in Ramallah, Palestine. The topic is socially sensitive in a context where marriage remains closely tied to family reputation, kinship networks, and long-term social security. A descriptive-analytical design was used. Data were collected from 50 parents of children with ASD through a structured questionnaire covering demographic characteristics and four substantive domains: psychological impact, social impact, economic burden, and family adaptation. Descriptive analysis showed consistently high levels of psychological stress, future-oriented worry, and emotional exhaustion among parents. Respondents also reported substantial social pressure, including reduced participation in community life, perceived lack of social acceptance, and concern that the presence of a child with ASD could negatively affect the marriage opportunities of siblings. Economic strain was another prominent pattern, with families reporting heavy therapy and rehabilitation costs and, in some cases, reduced work participation by one caregiver. At the same time, many families described adaptive responses, including shared caregiving responsibilities, the development of coping strategies, and stronger internal family solidarity. The findings suggest that the perceived effect on siblings’ marriage prospects is shaped less by autism itself than by stigma, misconceptions about heredity, and community attitudes toward disability. The paper recommends awareness initiatives, psychosocial support for families, and policy measures that reduce stigma and strengthen inclusion in Palestinian society.
Keywords: Autism Spectrum Disorder; Marriage Prospects; Siblings; Stigma; Family Reputation; Palestine; Ramallah